Mechanism of Action of Shenerjiangzhi Formulation on Hyperlipidemia Induced by Consumption of a High-Fat Diet in Rats Using Network Pharmacology and Analyses of the Gut Microbiota - Zhang, Shuang; Wang, Yu; Lu, Fang; Mohammed, Shadi A. D.; Liu, Hanxing; Ding, Song; Liu, Shu-min (Frontiers in Pharmacology, 2022)
Shenerjiangzhi formulation (SEJZ) is a new traditional Chinese medicine formulation (patent number: CN110680850A). SEJZ contains Eleutherococcus senticosus (Rupr. & Maxim.), Maxim. (Araliaceae; E. senticosus radix & rhizome), Lonicera japonica Thunb (Caprifoliaceae; Lonicera japonica branch, stem), Crataegus pinnatifida Bunge (Rosaceae; Crataegus pinnatifida fruit), and Auricularia auricula. SEJZ has been designed to treat hyperlipidemia. Despite the therapeutic benefits of SEJZ, its underlying mechanism of action is not known. We explored the efficacy of SEJZ against hyperlipidemia by integrating network pharmacology and 16S rRNA gene sequencing, and elucidated its mechanism of action. First, SEJZ targets were found through the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform and from the literature. Hyperlipidemia-related therapeutic targets were obtained from GeneCards, Online Mendelian Inheritance in Man, and DrugBank databases. Then, Search Tool for the Retrieval of Interacting Genes/Proteins and Cytoscape were applied for the analyses and construction of a protein–protein interaction (PPI) network. The Kyoto Encyclopedia of Genes and Genomes database was employed to identify signaling pathways that were enriched. Second, the therapeutic effects of SEJZ against hyperlipidemia induced by consumption of a high-fat diet (HFD) in rats were evaluated by measuring bodyweight changes and biochemical tests. SEJZ treatment was found to alleviate obesity and hyperlipidemia in rats. Finally, 16S rRNA gene sequencing showed that SEJZ could significantly increase the abundance of short-chain fatty acid-producing bacteria, restore the intestinal barrier, and maintain intestinal-flora homeostasis. Using PICRUSt2, six metabolic pathways were found to be consistent with the results of network pharmacology: “African trypanosomiasis”, “amoebiasis”, “arginine, and proline metabolism”, “calcium signaling pathway”, “NOD-like receptor signaling pathway”, and “tryptophan metabolism”. These pathways might represent how SEJZ works against hyperlipidemia. Moreover, the “African trypanosomiasis pathway” had the highest association with core genes. These results aid understanding of how SEJZ works against dyslipidemia and provide a reference for further studies.